2018
DOI: 10.1007/s11262-018-1549-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Salmonella pullorum bacteriophage YSP2 and its use as a therapy for chicken diarrhea

Abstract: Salmonella pullorum is the major pathogen that is harmful to the poultry industry in developing countries, and the treatment of chicken diarrhea caused by S. pullorum has become increasingly difficult. In this study, a virulent bacteriophage YSP2, which was able to specifically infect Salmonella, was isolated and characterized. Phage YSP2 was classified in the Siphoviridae family and had a short latent period of 10 min. No bacterial virulence- or lysogenesis-related ORF is present in the YSP2 genome, making it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
1
27
0
3
Order By: Relevance
“…Based on the results, we have concluded that the administration of phages was well tolerated at all examined doses, without any adverse effects that could be correlated with the bacteriophages' treatment. These findings are aligned with other scientific reports determining the safety of bacteriophage application in chicken broilers [25,[68][69][70][71]. For the final safety assessment of BAFASAL ® , we conducted two genotoxicity studies, i.e., the micronucleus test (MNA), and the Mouse Lymphoma Assay (MLA).…”
Section: Discussionsupporting
confidence: 71%
“…Based on the results, we have concluded that the administration of phages was well tolerated at all examined doses, without any adverse effects that could be correlated with the bacteriophages' treatment. These findings are aligned with other scientific reports determining the safety of bacteriophage application in chicken broilers [25,[68][69][70][71]. For the final safety assessment of BAFASAL ® , we conducted two genotoxicity studies, i.e., the micronucleus test (MNA), and the Mouse Lymphoma Assay (MLA).…”
Section: Discussionsupporting
confidence: 71%
“…In fact, many papers have been published recently which described bacteriophages that might be used in phage therapy against Salmonella . They include reports on characterization of previously unknown bacteriophages having the potential for use in phage therapy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], experimental studies with bacteriophages applied to poultry [ 21 , 22 , 23 , 24 , 25 , 26 ], and the use of bacteriophages in experimental phage therapy in mouse [ 27 , 28 , 29 , 30 ] or pig [ 31 ] models. Although promising results were obtained in these studies, and economic analyses have been performed to assess costs and benefits of the use of phage therapy for the control of Salmonella in poultry [ 9 , 32 ], it is evident that the host range of the vast majority of Salmonella phages is restricted to specific strains or serovars.…”
Section: Introductionmentioning
confidence: 99%
“…Según los trabajos realizados, el pH = 7 es el óptimo para estos virus, observándose reducción de títulos de fagos a medida que disminuye el pH y no resisten a medios muy ácidos con pH < 3. Teniendo en cuenta que el pH gástrico de los pollos es aproximadamente 2,8 [25], es natural que muchos se pierdan en ese tramo del tracto digestivo y es necesario protegerlos [22,23,25]. Además, se observó disminución de títulos de fagos a temperatura de 70°C durante 40 min o más y que no resisten temperaturas mayores o iguales a 80°C [23], por lo que el proceso de peletizado o extrusión puede disminuir los títulos de fagos y es necesario protegerlos [23,25].…”
Section: Fagos Protegidosunclassified